Operation Strategy for a Low-Cost Easy-Operation Cassino Hexapod - Giuseppe Carbone; Aviral Shrot; Marco Ceccarelli (Applied Bionics and Biomechanics)
This paper presents operation strategies for a hexapod walking machine that has been designed and built at the Laboratory of Robotics and Mechatronics (LARM) at the University of Cassino. Special care has been addressed in proposing and describing a suitable mechanical design and architecture that can be easily operated by a PLC with on–off logic. Experimental tests are reported in order to show feasibility and operational capability of the proposed design.